2018
DOI: 10.1002/jcla.22720
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between platelet indices and ABO blood groups in healthy adults

Abstract: Background ABO blood groups have been suggested to have a high correlation with cardiovascular diseases (CVDs). It has also been postulated that platelet indices, including mean platelet volume (MPV) and platelet distribution width (PDW), are very important in the development and progression of CVDs. However, despite these common associations with CVDs, as far as we know, there are no studies investigating platelet indices in ABO blood groups. Thus, the aim of this study was to investigate whether platelet ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
1
3
1
Order By: Relevance
“…Furthermore, MPV in the O-type individuals was fundamentally low compared to the non-O blood type individuals. 18,19 Even the platelet level was similar, as noted in our study. No significant difference was noted in the platelet counts and MPV for blood groups which strengthened the previous study.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, MPV in the O-type individuals was fundamentally low compared to the non-O blood type individuals. 18,19 Even the platelet level was similar, as noted in our study. No significant difference was noted in the platelet counts and MPV for blood groups which strengthened the previous study.…”
Section: Discussionsupporting
confidence: 90%
“…This is in consonance with the findings of a previous study that reported no significant differences in the mean platelet count between the different ABO blood groups. 12,13 In the present study there was insignificant differences when the fibrinogen level and platelets count compared with the age and gender. this similar Okeke and Iloka et al result which showed no significant differences in the mean level of both fibrinogen and platelet count in male and female participants of different ABO blood groups studied.…”
Section: Discussioncontrasting
confidence: 42%
“… 24 The B blood group subjects had reportedly high platelet distribution width, compared to A and O indicating the activation of platelets and the process of inflammation. 25 …”
Section: Discussionmentioning
confidence: 99%
“…24 The B blood group subjects had reportedly high platelet distribution width, compared to A and O indicating the activation of platelets and the process of inflammation. 25 In a study, von Willebrand factor (VWF) levels were elevated among subjects with BB genotype. 26 It is unclear how blood type B affects the VWF levels.…”
Section: A H E a D O F P R I N Tmentioning
confidence: 99%